Intra- and inter-rater reliability of the modified tuck jump assessment - Fort-Vanmeerhaeghe, A.; Montalvo, A. M.; Lloyd, R. S.; Read, P.; Myer, G. D. (Journal of Sports Science & Medicine, 2017)
The Tuck Jump Assessment (TJA) is a clinician-friendly screening tool that was designed to support practitioners with identification of neuromuscular deficits associated with anterior cruciate ligament injury. This study aimed to evaluate the inter- and intra-rater reliability of the modified scoring (0 to 2) TJA to add an additional range of objectivity for each criterion. A total of 24 elite youth volleyball athletes (12 males and 12 females) were included in this study. Each participant`s recorded performance of the TJA was scored independently by two raters across ten criteria using the modified scale. The two raters then scored the same videos one week later. Another investigator who was blind to the identity of the raters analyzed the scores from both raters for each participant. Kappa coefficient (k) and percentage of exact agreement (PEA) for both intra- and inter-rater reliability were analyzed for each item. Intraclass correlation coefficients (ICC) were calculated to determine intra- and inter-rater reliability of the modified TJA total score. Intra- and inter-rater k was good to excellent for most items (0.65-0.91). Average PEA between the two raters and two sessions ranged from 83.3 to 100% in all scored items. The ICC for the total score was excellent in both inter- and inter-rater correlations (0.94-0.96). This research demonstrated that the modified version of the TJA predominantly shows good to excellent intra- and inter-rater reliability in all analyzed criteria.